Peningkatan Kemampuan Membaca Permulaan Menggunakan Metode Fernald Di Panti Asuhan X Gresik - Naurah Hidni Zahirah; Setyani Alfinuha (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2023)
The ability to read is an indispensable competency for every individual, one of the reading skills is the ability to read beginning for low grade elementary school students. By reading, individuals are able to communicate or understand knowledge for their purposes. The subject of this research is a grade I elementary school student with low reading skills. The purpose of this study to improve the subject’s reading ability using the fernald method so the subject is able to understand the reading that is read. The research method used is quantitative with Single Subject Research (SSR) design with data analysis using quantitative descriptive analysis in the form of graph analysis. The conclusion in this study is that the use of the fernald method can improve the subject’s beginning reading ability.